ANALYSIS OF DIFFERENCES IN THE EFFECT OF REGIONAL ORIGINAL INCOME, GENERAL ALLOCATION FUNDS, AND SPECIAL ALLOCATION FUNDS ON REGIONAL CAPITAL EXPENDITURES IN REGENCIES AND CITIES IN CENTRAL JAVA IN PREPANDEMIC CONDITIONS AND THE NEW NORMAL ERA - Gabriella Arsani Linggom Silalahi; Aris Eddy Sarwono; Dewi Saptantinah Puji Astuti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This research aims to examine the impact of regional original income, general allocation funds, andspecial allocation funds on regional capital expenditures in Central Java in pre-pandemic conditionsand the new normal era. The analysis was carried out in 2018 and 2019, before the Covid-19pandemic, and in 2020 and 2021, during the new normal era. The APBD realization findings for eachdistrict and city in Central Java can be found in the Directorate General of Fiscal Balance(https://djpk.kemenkeu.go.id), which serves as the data source for this research. A total of 35regencies and cities were sampled, with 29 regencies and six towns. Multiple linear regressionanalysis, validity testing, reliability testing, classical assumption testing, and the OLS (Ordinary LeastSquares) method are utilized in the study, which is assessed to use the Statistical Package for theSocial Sciences (SPSS). This research finds Regional Original Income, General Allocation Funds,and Special Allocation Funds for Regional Capital Expenditures in Central Java. In the two yearspreceding the pandemic, 2018 and 2019, the Regional Original Income variable had a significanteffect. In contrast, the variables for the General Allocation Fund and the Special Allocation Fundindicated having no significant effect. Regional Original Income, General Allocation Funds, andSpecial Allocation Funds have a significant effect on Central Java Regional Capital Expenditures inthe new normal era, which begins in 2020 and continues through 2021.Keywords: Regional Original Income, General Allocation Fund, Special Allocation Fund,Regional Capital Expenditure.